Examining the potential of community design to limit human conflict with white‐tailed deer - Dawn A. Gorham; William F. Porter (Wildlife Society Bulletin)
Abstract Modification of habitat has the potential to be both less costly and less controversial than direct management of white‐tailed deer (Odocoileus virginianus) populations in addressing problems related to suburban deer overabundance. A novel approach to reducing deer–human conflict would involve anticipating issues of deer management when communities are designed. We tested the hypothesis that the compact character of traditional neighborhood designs will result in reduced habitat suitability for deer as compared to suburban‐sprawl patterns of development. We evaluated landscape pattern and estimated deer densities in 2 communities in upstate New York, USA, and then predicted habitat condition and potential deer densities in different types of development. Comparisons of the habitat conditions in the neighborhood versus sprawl areas revealed significant differences in the amount of edge between the tree and lawn class (P < 0.05), with sprawl development having a greater tree–lawn edge density. Both field and tree disjunct core‐area densities were significantly higher in areas of sprawl development (P < 0.01). Increasing amounts of field and the distribution of tree canopy across the landscape were associated with increased deer densities. In the suburban environment, where food is abundant, the availability of cover throughout the landscape becomes an important factor affecting deer density. © 2011 The Wildlife Society.